Der betende Sünder vor Gott : Studien zu Vergebungsvorstellungen in urchristlichen und frühjüdischen Texten - Stemm, Sönke v. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1999)
This volume provides important new insights into the concept of \'forgiveness\' in early Christian literature. In contrast to much of the existing literature on the notion of forgiveness, which usually focuses on the preconditions for being forgiven, the author sets out to describe the actual meanings and connotations of this concept during the period in which the New Testament was being formed. In early Christian texts the notion of forgiveness is expressed in a variety of ways. On the basis of detailed analysis of a number of early Christian and contemporary Jewish prayers the author uncovers an array of different shades of meaning, which often can be obscured in modern translations. In so doing he demonstrates the importance of this complex of meanings for early Christians, not only as part of their soteriology, but in their overall theological outlook as well.